2012
DOI: 10.4018/jebr.2012010104
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Intention to Use Mobile Coupon and the Moderating Effects of Price Consciousness and Gender

Abstract: Research on the development, intention to use, and the use of mobile coupons is scanty, particularly in developing countries such as Malaysia. Therefore, this paper examines consumers’ intention to use mobile coupon (m-coupon). The authors considered several factors and developed the conceptual framework underpinned on an extended Technology Adoption Model (TAM). The data analysis was based on 781 valid responses from four locations in Malaysia. The results indicate that perceived usefulness, attitude, and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
(69 reference statements)
1
19
1
Order By: Relevance
“…H4: Good economic conditions will have a positive influence on attitude towards advertising 2.1.5 Social Integration Munusamy and Wong (2007) reported that social integration role of advertising means that it presents lifestyle imagery, and its communication goals often indicate a brand image or personality, the representation of typical or idealized users, associated status or prestige, or social reactions to purchase, own and use (Jayasingh & Eze, 2012). The role of advertising in educating children can be viewed as an element of children's socialisation and their social integration in view of formation of role models, aspirations and social images, as demonstrated.…”
Section: Economic Conditionmentioning
confidence: 99%
“…H4: Good economic conditions will have a positive influence on attitude towards advertising 2.1.5 Social Integration Munusamy and Wong (2007) reported that social integration role of advertising means that it presents lifestyle imagery, and its communication goals often indicate a brand image or personality, the representation of typical or idealized users, associated status or prestige, or social reactions to purchase, own and use (Jayasingh & Eze, 2012). The role of advertising in educating children can be viewed as an element of children's socialisation and their social integration in view of formation of role models, aspirations and social images, as demonstrated.…”
Section: Economic Conditionmentioning
confidence: 99%
“…The articles refer to topics about consumers' attitudes (Barutçu, 2007(Barutçu, , 2008Khare and Rakesh, 2012;Megdadi and Nusair, 2011;Persaud and Azhar, 2012) and permission (Jayawardhena et al, 2009) towards m-marketing themes, or they provide an overview of m-marketing in the retailing environment (Shankar et al, 2011). Moreover, various m-marketing applications and tools, such as mobile advertising (Chen and Hsieh, 2012;Hosbond and Skov, 2007;De Reyck and Degraeve, 2003), mobile couponing (Cameron et al, 2012;Jayasingh and Eze, 2012), mobile payment (Daskapan et al, 2010;Smith and Sankaranarayanan, 2012) and topics around multi-channel retailing (Barlow et al, 2004;Broeckelmann, 2010;Lin, 2012) are already subjects of study. Thus, the relevant topics can be broadly clustered around two areas of interest:…”
mentioning
confidence: 99%
“…The results of the study show that users perceive push and pull m-marketing activities as helpful and value-adding in the context of navigation and shopping if they are personalized (fit the users' preference and interests best), location-based, time-aware and consider the users' current activity. In addition, the level of acceptance is distinguished by demographic characteristics (age, income, education background, occupation, and employment) and by the kind of m-marketing activity (Barutçu, 2007(Barutçu, , 2008Broeckelmann, 2010;Chen and Hsieh, 2012;Hosbond and Skov, 2007;Jayasingh and Eze, 2012;Jayawardhena et al, 2009;Khare and Rakesh, 2012;Kurkovsky and Harihar, 2006;Megdadi and Nusair, 2011;De Reyck and Degraeve, 2003;Persaud and Azhar, 2012). De Reyck and Degraeve (2003) discovered an additional value for customers if they only receive push-based SMS advertising on their mobile phones while inside a shopping centre.…”
mentioning
confidence: 99%
“…Each item loads to its designated factor (variable), which indicates strong convergent validity. FA shows items' consistency with the instrument's underlying structure and reflects the factors identified from prior literature (Bagozzi, Yi & Phillips, 1991;Klopping & McKinney, 2004;Eze, 2008;Jayasingh & Eze, 2012).…”
Section: Data Analysis and Findingsmentioning
confidence: 89%